Subacute toxicity evaluations of LPM3480392 in rats, a full µ-opioid receptor biased agonist - Liang Ye; Chunmei Li; Wanglin Jiang; Yifei Yang; Wenyan Wang; Haibo Zhu; Zhengping Hu; Ning Li; Xiaobo Cen; Hongbo Wang; Jingwei Tian (Frontiers Media S.A., 2023)
Opiates produce analgesia via G-protein signaling, and adverse effects, such as respiratory depression and decreased bowel motility, by β-arrestin pathway. Oliceridine, a G protein-biased MOR agonist, only presents modest safety advantages as compared to other opiates in clinical trials, possibly due to its limited bias. Our previous study shown that LPM3480392, a full MOR biased agonist, is selective for the Gi pathway over the β-arrestin-2. In the present article, we evaluated the subacute toxicity of LPM3480392 in rats. The rats were administered with control article or LPM3480392 0.6, 1.2 or 2.4 mg/kg/day for 4 consecutive weeks followed by a 4-week recovery phase. Intravenous infusion was conducted at tail vein at 0.2, 0.4 or 0.8 mg/kg/day with a dosing volume of 10 mL/kg and 5 min/rat/dose, three times a day with an interval of approximately 4 h. The concomitant toxicokinetics study was conducted. Two unscheduled rats at 2.4 mg/kg/day died with no clear cause. For the scheduled necropsy, the major effects were associated with the MOR agonist-related pharmacodynamic properties of LPM3480392 (e.g., increased activity, increased muscle tone; decreased food consumption and body weight gain; and clinical chemistry changes related with decreased food consumption) in three LPM3480392 groups. In addition, LPM3480392 at 2.4 mg/kg/day also induced deep respiration and histopathology changes in testis and epididymis in sporadic individual rats. However, different from other opiates, LPM3480392 presents weak/no immunosuppression and the decreased adrenal gland weight, which may be due to LPM3480392' full MOR bias. At the end of recovery phase, all findings were recovered to some extent or completely. In the toxicokinetics study, the dose-dependent elevation of drug exposure was observed, which partly explained the toxicity of high dose. In summary, LPM3480392 has exhibited good safety characteristics in this subacute toxicity study in rats.